Macau’s elephant and mammoth ivory trade today - Esmond Martin; Lucy Vigne (Pachyderm)
This article presents the results of a survey of the ivory trade in Macau carried out in 2015. Macau was once one of the largest centres for the ivory trade in Southeast Asia. In the early 1980s the Portuguese territory of Macau was a major importer of tusks from Africa and also a large processor of ivory, especially jewellery, for the Hong Kong market. The trade since then has declined sharply. At the time of a previous survey in 2004, there was only one ivory craftsman left and just 1,718 ivory items were counted on display for sale in 21 retail shops. In 2015 only 326 ivory items were counted, representing a decline of 81% in 11 years, and not a single ivory craftsman was active. The number of outlets seen with worked ivory, remained much the same as 11 years ago (21 in 2004 and 22 in 2015). Most shops, however, had changed, and those previously selling large numbers of newer ivory items had left the trade. In 2015, the majority of shops selling ivory displayed only a few, antique items. Millions of Chinese mainlanders now visit Macau annually; they spend nearly all their time and money on gambling in the fast-developing casino industry, and have little interest in purchasing ivory. Profit margins are too low for ivory vendors to display large stocks of new worked ivory and thus only a sprinkling of old or antique items was seen in the shops. From 2004 to 2015 the number of mammoth ivory items for sale in Macau rose from 151 to 590; however, the number of shops selling mammoth ivory only rose slightly, from four to five, between 2004 and 2015. The amount of mammoth ivory on sale in Macau is still relatively tiny and, similar to elephant ivory, the trade in mammoth ivory looks unlikely to expand significantly under present circumstances.